Econometric methods of risk assessment of innovative projects - Zianko, V. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The most common methods of risk assessment of innovative projects are analyzed in the article. Their advantages and disadvantages are explored. The expediency of their integrated use is substantiated.